Seroepidemiology of enterovirus D68 infection in China - Zichun Xiang; Linlin Li; Lili Ren; Li Guo; Zhengde Xie; Chunyan Liu; Taisheng Li; Ming Luo; Gláucia Paranhos-Baccalà; Wenbo Xu; Jianwei Wang (Emerging Microbes and Infections, 2017)
Human enterovirus 68 (EV-D68) is a rarely reported virus that has been linked to respiratory disease. In recent years, reports about EV-D68 infection have markedly increased worldwide. However, the epidemiological features of this emerging infection are not well understood. To evaluate the emerging EV-D68 epidemic, we isolated the circulating viral strain and investigated the seroprevalence of neutralizing antibodies (NAbs) in Beijing between 2004 and 2011. We found that the titers of EV-D68 NAbs were generally low in all age groups in sampled populations in 2004 but significantly higher in 2009. From 2007 to 2011, the NAbs against EV-D68 significantly increased over time. These findings indicate that EV-D68 has spread widely in the Chinese population in recent years, although only a limited number of cases were reported.Emerging Microbes & Infections (2017) 6, e32; doi:10.1038/emi.2017.14; published online 10 May 2017